Pengaruh Game Mobile Legends dan Media Sosial terhadap Perubahan Bahasa Indonesia di Kalangan Remaja - Eunike Priskila Yogyanti Boru Pardede; Mely Syahputri Sidauruk; Sonia Nuansa Indah Sihombing; M. Surip (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to examine the influence of the Mobile Legend game and social media on changes in the use of Indonesian among teenagers. Using an online survey method with a quantitative and qualitative approach, data was obtained from a survey of 34 teenagers aged 12-21 years. The research results showed that as many as 47.05% of respondents felt that playing Mobile Legends made them use harsh language more often, both when playing games and in daily interactions with friends or family. As many as 47.05% of respondents stated that they often used harsh language. slang and abbreviations in daily conversations, as many as 42.6% of respondents are aware of maintaining a balance between the use of slang and standard language. As many as 29.4% of respondents feel more comfortable and use slang more often due to the influence of social media. This research concludes that the Mobile Legend game and social media have a significant influence on the use of informal language and foreign terms among teenagers, which has an impact on their ability to speak formal language.